Nazi crimes and the law - Stoltzfus, Nathan 1954- Hrsg; Friedlander, Henry 1930-2012 (Publications of the German Historical Institute, 2008)
Nazi crimes and the German law / Henry Friedlander -- The setting and significance of the Nuremberg trials : a historian's perspective / Gerhard L. Weinberg -- The American military commission trials of 1945 / Patricia Heberer -- Punishing the excess : sadism, bureaucratized atrocity, and the U.S. Army concentration camp trials, 1945-1947 / Michael S. Bryant -- Perceptions and suppression of Nazi crimes by the postwar German judiciary / Joachim Perels -- Getting away with murder : the Täubner case / Dick de Mildt -- "A great achievement of German troops in mountain warfare" : Cold War pressures and the German prosecution of Wehrmacht war crimes in the case of Cephalonia, 1943 / Nathan Stoltzfus -- The trials of Nazi war criminals in Austria / Winfried R. Garscha -- The German-German rivalry and the prosecution of Nazi war criminals during the Cold War, 1958-1965 / Annette Weinke -- History in the courthouse : the presentation of World War II crimes in U.S. courts sixty years later / Elizabeth B. White -- Law, history, and holocaust denial in the courtroom : the Zündel and Irving cases / Christopher R. Browning